Impact on mortality following first acute myocardial infarction of distance between home and hospital: cohort study. Issue 9 (5th November 2007) - Wei, L; Lang, C C; Sullivan, F M; Boyle, P; Wang, J; Pringle, S D; MacDonald, T M
Abstract : Objective: To investigate the effect of distance between home and acute hospital on mortality outcome of patients experiencing an incident myocardial infarction (MI). Design: Cohort study using a record linkage database. Setting: Tayside, Scotland, UK. Patients: 10 541 patients with incident acute MI between 1994 and 2003 were identified from Tayside hospital discharge data and from death certification data. Main outcome measures: MI mortality in the community, all-cause mortality in hospital and all-cause mortality during follow-up. Results: 4133 subjects died following incident MI in the community (that is, were not hospitalised), 6408 patients survived to be hospitalised and 1010 of these (15.8%) died in hospital. Of 5398 discharged from hospital, 1907 (35.3%) died during a median of 3.2 years of follow-up. After adjustment for rurality and other known risk factors, distance between home and admitting hospital was significantly associated with increased mortality both before hospital admission (adjusted odds ratio (OR), 2.05, 95% CI 1.00 to 4.21 for >9 miles and 1.46, 1.09 to 1.95 for 3–9 miles when compared to <3 miles) and after hospitalisation (adjusted hazard ratio (HR) 1.90, 1.19 to 3.02 and 1.27, 0.96 to 1.68). However, there was no effect of distance on in-hospital mortality (adjusted OR 0.95, 0.45 to 2.03 and 1.02, 0.66 to 1.58). Conclusion: The distance between home and hospital of admission may predict mortality in subjects experiencing a first acute MI. This association was found both before and after hospitalisation. Further studies are needed to explore the reasons for this association. However these data provide support for policies that locate services for acute MI closer to where patients live.